Literature Review: Implementasi Konfrontasi Diri sebagai Strategi Komunikasi Terapeutik dalam Keperawatan Keluarga - M Bachtiar Safrudin; Kartika Setia Purdani; Aisyah Nur Sabila; Risnawati Sari; Anita Pasha; Ikhram Haniyyu Muhni; Kamila Candra Maulani; Mareta Anggi Saputri; Marlina Damayanti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Self-confrontation is a therapeutic communication technique that aims to enhance self-awareness, emotional regulation, and coping abilities across various groups, including families within nursing practice. This literature review aims to examine the effectiveness of self-confrontation techniques in family nursing based on studies published between 2021 and 2025. The findings indicate that self-confrontation can strengthen self-control, emotional stability, social skills, and adherence to positive behaviors, particularly when combined with self-reflection and muhasabah practices. In mental health nursing, the use of confrontation for hallucinations has been shown to reduce symptoms and improve reality orientation when supported by education, structured activities, and family involvement. The success of this technique is also strongly influenced by therapeutic communication that is empathetic and nonjudgmental. Evidence related to emotional intelligence and coping strategies further highlights that emotional regulation plays a crucial role in the effectiveness of self-confrontation. Overall, self-confrontation is effective in family nursing when applied professionally, at the appropriate time, and supported by a compassionate approach. This review provides a comprehensive understanding of the contribution of confrontation techniques to strengthening therapeutic communication and enhancing family adaptive functioning within nursing services.